2013
DOI: 10.1590/s0080-62342013000100014
|View full text |Cite
|
Sign up to set email alerts
|

A produção do cuidado a usuários com hipertensão arterial e as tecnologias em saúde

Abstract: RESUMOObje vou-se com este trabalho analisar a u lização da tecnologia das relações na produção do cuidado a usuários com hipertensão arterial. Trata-se de estudo qualitavo, realizado em oito Unidades de Saúde da Família de Jequié-BA. Os sujeitos do estudo foram formuladores da polí ca, profi ssionais de saúde e usuários, totalizando dezesseis informantes. Em 2010, realizou--se entrevista semiestruturada, observação sistemá ca e análise documental. Para apreciação dos dados u lizou-se análise de conteúdo temá … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
13

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 8 publications
0
11
0
13
Order By: Relevance
“…21 This work process reveals a relationship where the disciplinary power 22 operates defining spaces, relationships and where scientific knowledge and professional decision are sovereign, reducing drastically and dramatically the possibility of user participation in the design of their therapeutic plan. 14 A study conducted in a city of Bahia has also identified the high consumption of light-hard and hard technologies practices in attention to hypertensive patients and noted a certain weakness of PHC professionals in performing sensitive listening to the person with hypertension, giving voice to their demands and needs, a result that, for authors 5 , continues as one of the main challenges to change care practices for hypertension: focus care on the user and not on procedures. 14 The organization of "live in action" work is directly influenced by micropolitics 10-1 issues and it is necessary that health professionals identify new senses in care production, taking light technologies as guides for the use of light-hard and hard technologies.…”
Section: :100mentioning
confidence: 99%
See 1 more Smart Citation
“…21 This work process reveals a relationship where the disciplinary power 22 operates defining spaces, relationships and where scientific knowledge and professional decision are sovereign, reducing drastically and dramatically the possibility of user participation in the design of their therapeutic plan. 14 A study conducted in a city of Bahia has also identified the high consumption of light-hard and hard technologies practices in attention to hypertensive patients and noted a certain weakness of PHC professionals in performing sensitive listening to the person with hypertension, giving voice to their demands and needs, a result that, for authors 5 , continues as one of the main challenges to change care practices for hypertension: focus care on the user and not on procedures. 14 The organization of "live in action" work is directly influenced by micropolitics 10-1 issues and it is necessary that health professionals identify new senses in care production, taking light technologies as guides for the use of light-hard and hard technologies.…”
Section: :100mentioning
confidence: 99%
“…3 Studies show that attention to hypertensive patients in PHC services still comes down to the supply of medicines, laboratory tests, and medical appointments. [4][5] Thus, it is evident the need to redirect the performance of health workers, strengthen health promotion strategies and prevention of complications and organize the healthcare network for chronic noncommunicable diseases in the context of comprehensive care to the user living with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing education of the team must always be on the agenda in the aiming at raising awareness of the population to change their habits of life. Furthermore, the interaction between the different actors of care is crucial, including the collective planning of actions, more critical monitoring of the health situation of the population and the incentive to involve families and the different social segments that are directly or indirectly linked to the treatment of SAH [16].…”
Section: W12mentioning
confidence: 99%
“…A ESF propõe-se as superar práticas estritamente curativas, fragmentadas, em que predominam a preocupação e a realização de procedimentos, utilização de equipamentos e reprodução de normas preestabelecidas, como o cuidado em si, que muitas vezes não atendem às necessidades de saúde das famílias e usuários. 13,14 Tendo em vista os pressupostos descritos, as falas dos sujeitos foram analisadas e discutidas destacando-se as visões que os profissionais apresentam sobre o funcionamento da equipe na atenção à saúde do hipertenso e, mais especificamente, ao papel do enfermeiro.…”
Section: Tr Ajetória Metodológicaunclassified